Strategic customer management : integrating relationship marketing and CRM / Adrian Payne; Pennie Frow - Payne, Adrian
"The strategic management of customer relationships is a critical activity for all enterprises. The means of effectively managing relationships with customers are typically addressed under the headings of relationship marketing and customer relationship management (CRM), to name but two terms used to describe the management of customer relationships"